Investigation on the Effect of Probability Distribution on the Dynamic Response of Liquefiable Soils - Juncheng Wang; Li Zhou; Wenzhi Song; Houle Zhang; Yongxin Wu (Advances in Civil Engineering)
This study investigated the effect of different probabilistic distributions (Lognormal, Gamma, and Beta) to characterize the spatial variability of shear modulus on the soil liquefiable response. The parameter sensitivity analysis included the coefficient of variation and scale of fluctuation of soil shear modulus. The results revealed that the distribution type had no significant influence on the liquefication zone. In particular, the estimation with Beta distribution is the worst scenario. It illuminated that the estimation with Beta distribution can provide a conservative design if site investigation is absent.